HUBUNGAN PENGETAHUAN REMAJA DENGAN PERILAKU PEMERIKSAAN PAYUDARA SENDIRI (SADARI) - Mariyati; Ida Suryawati; Nur Afni (Sekolah Tinggi Ilmu Kesehatan Muhammadiyah Lhokseumawe, 2022)
Breast self-examination (BSE) is of paramount importance for women, especially teenagers, as an effort to find out the possibility of breast cancer or lumps that can develop into breast cancer. The purpose of this study was to determine the relationship between adolescent knowledge and BSE behavior.Descriptive corraletion with a cross sectional approach was used in this study.This study used total sampling technique with 40 people as respondents. The data was analyzed by computerization through univariate and bivariate analysis with statistical tests using Chi-Square.This study found that 30% of adolescents did not know and did not perform BSE, 20% of them were categorized as having less sufficient knowledge and performed BSE, 17.5% had good knowledge and performed BSE, 15% were having less sufficient knowledge but did not perform BSE, 15% were having less sufficient knowledge but performed BSE, and 2.5% were having good knowledge but did not perform BSE. The results of P-value was 0.035 <0.05, meaning that there is a relationship between adolescent knowledge and conscious behavior, with an OR of 7.287.